2012
DOI: 10.1111/bjh.12120
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of bendamustine for the treatment of patients with recurring Hodgkin lymphoma

Abstract: SummaryThe management of patients with Hodgkin lymphoma (HL) recurring after stem cell transplantation (SCT) and multiply relapsed disease remains challenging. We report on 41 such patients who received bendamustine hydrochloride, a bifunctional mechlorethamine derivative mechanistically unrelated to traditional alkylators, after a median of four prior chemotherapy lines, including SCT in 85% of cases. Bendamustine was given at doses of 90-120 mg/m 2 every 21 or 28 d. At first assessment (2-4 cycles), the over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0
6

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 34 publications
3
49
0
6
Order By: Relevance
“…Nevertheless, approximately 5-10% of HL patients are refractory to initial treatment and 10-30% relapse after achieving an initial complete remission. In this refractory setting, disease-free survival is very short, [1][2][3][4] even when using an aggressive chemotherapy combination (platinum-based, ifosfamide/etoposide-based). 3,[5][6][7] Owing to these poor results, most experts recommend that eligible patients with relapsed or refractory disease undergo intensive therapy (auto-or allograft) after obtaining a good response.…”
mentioning
confidence: 99%
“…Nevertheless, approximately 5-10% of HL patients are refractory to initial treatment and 10-30% relapse after achieving an initial complete remission. In this refractory setting, disease-free survival is very short, [1][2][3][4] even when using an aggressive chemotherapy combination (platinum-based, ifosfamide/etoposide-based). 3,[5][6][7] Owing to these poor results, most experts recommend that eligible patients with relapsed or refractory disease undergo intensive therapy (auto-or allograft) after obtaining a good response.…”
mentioning
confidence: 99%
“…Hatásme-chanizmusa kettős, mivel apoptózist indukál a p53-dependens alkiláló aktivitásán keresztül, illetve DNS-káro-sító, ami erőteljesebb és hosszabban tartó, mint más alkilálószereké [34]. Relabáló és refrakter HL-ben több vizsgálat igazolta hatékonyságát [35,36,37], a bendamustint 120 mg/m 2 dózisban 2 napig, 28 naponta alkalmazva. Az ORR 53 és 78%, a CR 33 és 29% volt [36,37].…”
Section: Bendamustinunclassified
“…Relabáló és refrakter HL-ben több vizsgálat igazolta hatékonyságát [35,36,37], a bendamustint 120 mg/m 2 dózisban 2 napig, 28 naponta alkalmazva. Az ORR 53 és 78%, a CR 33 és 29% volt [36,37]. A leggyakoribb grade 3 vagy súlyosabb mellékhatá-sok a thrombocytopenia (20%), az anaemia (14%) és az infekciók (14%) voltak [36].…”
Section: Bendamustinunclassified
“…19 A retrospective study reported an ORR of 78% using bendamustine in relapsed HL. 20 The Memorial Sloan-Kettering Cancer Center group conducted a phase 2 study of bendamustine in 36 (75% had relapsed after a prior auto-HCT) patients with relapsed/refractory HL. 21 The ORR was 53% (CR ¼ 33%).…”
Section: Salvage Therapies For Relapsed Hl After Auto-hctmentioning
confidence: 99%